Tema 2: Open Roberta - A Web Based Approach to Visually Program Real Educational Robots - Ketterl, Markus; Jost, Beate; Leimbach, Thorsten; Budde, Reinhard (Tidsskriftet Læring og Medier (LOM), 2015)
The aim of the Open Roberta initiative is to support visual online programming of educational robots. The goal is to overcome technical and professional barriers for teachers and students alike at home or in the classrooms. The free to use cloud-based Open Roberta Lab consists of graphical programming tools for the browser that enable beginners to seamlessly start coding without long-winded system installations, setups or additional technology getting in the way. Open Roberta is a project within the Fraunhofer initiative ”Roberta - Learning with Robots”. A further aspect of the paper is the introduction of the NEPOR meta programming language as a core concept for coupling real educational robot systems.